(untitled) (Innovation & Development in Engineering and Applied Science, 2023)
The implementation of plant layout in companies allows the improvement of production processes in order to reduce production times. Within this study, several factors are analyzed to design the plant layout in order to satisfy, optimize and make more flexible the mobilization of machinery, products or operative personnel. The Guerchet Method is applied to determine the required surface area in a standard metal-mechanical factory, considering expansion plans and operational requirements. This scheme allows optimizing the available surface and complying with the minimum requirements for its execution. Therefore, a case study of a metal-mechanical factory is used to determine the static, gravitational and evolution surface. In addition, the ratio between the number of machines and the total area required is determined.